A Multi‐Method Database of the Black and White Marbles of Göktepe (Aphrodisias), Including Isotopic, EPR, Trace and Petrographic Data. (27th December 2013) - Attanasio, D.; Bruno, M.; Prochaska, W.; Yavuz, A. B.
Abstract : A database of the ancient marbles of Göktepe near Aphrodisias is reported, and includes 160 white, black and bichrome samples from 13 quarries and two waste deposits. The quarries are grouped into four districts. Districts 1 and 2, to the north, produced exclusively black or dark grey marbles ( nero antico ). Districts 3 and 4 produced white statuary marble. Nero antico and a black and white stone were also quarried in district 4, where the black marble surfaces again. The samples were characterized using petrography, isotopic analysis, EPR spectroscopy and trace analysis. The Göktepe white exhibits an unparalleled combination of fine grain, low EPR intensity and high strontium concentration that often allows easy identification. The isotopic values are less distinctive and similar to those for Carrara. In most cases, however, they are tightly grouped and also quite indicative. The black marbles exhibit a much weaker metamorphic overprint. With respect to the white marbles, they show analytical similarities but also notable differences. Therefore, establishing their provenance can be more difficult and may require the support of petrographic analysis. The results suggest that the Göktepe marbles were among the most prized and widespread statuary marbles used in Roman times, particularly from the early second centuryad onwards.